The role of ubiquitination and deubiquitination in cancer lipid metabolism - Xu, Yongkang; Zeng, Jiayu; Fu, Shumin; Liu, Kan; Mao, Ye; Tao, Si; Wu, Jianbing (Frontiers in Oncology, 2025)
The ubiquitin-proteasome system (UPS) is one of the main degradation systems within cells, catalyzing the tagging of proteins for degradation by ubiquitin molecules, which are then recognized and degraded by the proteasome. Lipid metabolism plays a crucial role in cellular energy metabolism and is closely associated with the occurrence and development of cancers. Recent research indicates that cancer lipid metabolism is regulated by intracellular proteins, including ubiquitination modifications. This review will explore the role of ubiquitination in regulating cancer lipid metabolism, summarize the latest research progress, and propose potential therapeutic strategies.